Pengaruh Kinerja Keuangan dan Corporate Governance terhadap Nilai Perusahaan Sub Sektor Perbankan - Lutfiatus Sholikhah; Rini Rahayu Kurniati; Khoiriyah Trianti (Universitas Trunojoyo Madura, 2024)
The aim of this study is to examine the impact of financial performance, namely earning per share (EPS) and debt to equity ratio (DER), as well as corporate governance, namely managerial ownership (MO) and institusional ownership (IO), on firm value measured by price to book value (PBV). Employing a quantitative approach, this research analyzes data extracted from the annual reports of 14 selected companies in the Banking sub-sector from 2018 to 2022. By employing purposive sampling technique, a total of 70 research samples were collected and analyzed using IBM SPSS version 27. The method utilized is multiple linear regression analysis. According to the research findings, earning per share (EPS), managerial ownership (MO), and institusional ownership (IO) in partial t-tests significantly influence firm value (PBV). Meanwhile, debt to equity ratio (DER) in partial t-tests does not significantly affect firm value (PBV). The results indicate that both financial performance (EPS and DER) and corporate governance (MO and IO) have significant impacts on firm value (PBV). The company must increase EPS and managerial ownership to attract investors and enhance its value. Additionally, effective management of DER is necessary to maintain financial stability. Good management of institutional ownership can enhance oversight and company performance, ultimately increasing the company’s value in the capital market